Association of bone mineralization markers with dietary nutrient intake in adolescents with and without biochemical osteomalacia - Al-Daghri, Nasser M.; Sabico, Shaun; Wani, Kaiser; Hussain, Syed Danish; Yakout, Sobhy; Aljohani, Naji; Uday, Suma; Högler, Wolfgang (Frontiers in Nutrition, 2023)
Dietary intake is widely known to play a crucial role in achieving peak bone mass among children and adolescents. Unfortunately, this information is lacking among Arab adolescents, an understudied demographic that has recently been observed to have a high prevalence of abnormal mineralization markers [low serum 25(OH)D, high serum alkaline phosphatase (ALP), low calcium (Ca) and/or inorganic phosphate (Pi)] suggestive of biochemical osteomalacia (OM, defined as any 2 of the 4 parameters). In order to fill this gap, we aimed to evaluate the associations of serum markers of biochemical OM with dietary intake of macronutrients, vitamins and trace minerals. Methods: Saudi adolescents (N=2938, 57.8% girls), aged 12-17 years from 60 different schools in Riyadh, Saudi Arabia were included. Dietary intake of nutrients was calculated following a semi-quantitiave 24-hour dietary recall over 3 weekdays and one weekend-day using a validated food frequency questionnaire. Compliance to reference daily intake (RDI) of macronutrients, vitamins and trace minerals were calculated. Fasting blood samples were collected and circulating levels of 25(OH)D, ALP, Ca and Pi were analyzed. Results: A total of 1819 (1083 girls and 736 boys) adolescents provided the dietary recall data. Biochemical OM was identified in 175 (9.6%) participants (13.5% in girls, 3.9% in boys; p<0.01) while the rest served as controls (N=1644). All participants had serum 25(OH)D levels <50nmol/l. Most participants had very low dietary intakes of Ca (median ~290mg) and vitamin D (median ~4µg) which are far below the RDI of 1300 mg/day and 20 µg/day, respectively. In contrast, excess dietary intakes of Pi, Na, K and Fe were observed in all participants. In the biochemical OM group, thiamine and protein intake were significant predictors of serum 25(OH)D, explaining 4.3% of the variance perceived (r=0.23, adjusted r2 = 4.3%, p=0.01). Among controls, dietary vitamin C and vitamin D explained 0.6% of the total variation in serum 25(OH)D (r=0.09, adjusted r2=0.6%, p=0.004). Conclusions: Arab adolescents do not meet the RDI for dietary Ca and vitamin D, and none have sufficient vitamin D status (25(OH)D levels >50 nmol/L) but they exceed the RDI for dietary Pi. (truncated)